OPTIMALISASI TINGKAT KEMATANGAN KESELAMATAN (SAFETY MATURITY LEVEL) SEKTOR PERTAMBANGAN NIKEL MELALUI KOLABORASI PT. PUTRA PERKASA ABADI JOB SITE MLP DAN DOSEN FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS HALU OLEO - Amirudin, Agus; Burhanudin, Faham; Saptaputra, Syawal Kamiluddin; Prianti, Indah Ade; Saktiansyah, La Ode Saktiansyah; Hikmawati, Zainab (Universitas Halu Oleo, 2023)
Nickel mining is a vital industry that plays an important role in providing energy supplies in Indonesia. Work activities in the nickel mining sector have high potential for danger and risk so that aspects are required to fulfill Safety, Occupational Health and Environmental requirements in every work activity. Based on Minister of Energy and Mineral Resources Regulation No. 26/2018 concerning the implementation of good mining principles and supervision of Minerba mining, it is explained that the Mining Safety Management System (MSMS) is part of the system in the company as a whole, helping companies to implement Mining Occupational Safety and Health (OSH) and Implementation of Operational Safety of Mining. The aim of this activity is to optimize the safety maturity level (Safety Maturity Level) of the mining sector through the collaboration of PT. Putra Perkasa Abadi MLP Job Site with FKM UHO lecturers. The collaboration methods used were interviews, Focus Group Discussions, observations, questionnaires, document reviews, data analysis and simulations. The result of this collaboration is to obtain an overview of the safety performance maturity level (Safety Maturity Level/SML) in the company in proactive category.